Students’ Perception about English Song and The Correlation Between Frequency of Listening to English Song and Students’ Performance in Listening Class (RETAIN, 2018)
AbstrakTujuan dari penelitian ini adalah untuk menambah opsi pada sumber pengajaran baik untuk dosen dan mahasiswa. pertanyaan dari penelitian ini adalah Bagaimana persepsi para mahasiswa terhadap bagaimana lagu berbahasa Inggris membantu mereka dalam belajar Bahasa Inggris? Dan apakah ada korelasi antara frekuensi mendengarkan lagu berbahasa Inggris dengan kemampuan mereka di kelas listening? Untuk menjawab pertanyaan penelitian tersebut, peneliti menggunakan metode survey research dengan bantuan dua instrumen, kuesioner dan catatan dosen. Para peserta untuk penelitian adalah 48 siswa dari dua kelas listening for daily content. Berdasarkan temuan penelitian, sebagian besar siswa menganggap bahwa lagu berbahasa Inggris membantu mereka untuk mencapai kemampuan yang baik di kelas. ini bisa dilihat dari tanggapan para peserta yang menjawab kuesioner. Juga, ada korelasi yang signifikan antara frekuensi mendengarkan lagu berbahasa Inggris dengan kemampuan siswa di kelas. para siswa yang sering mendengarkan lagu-lagu berbahasa Inggris dan menggunakannya sebagai media untuk belajar memiliki skor yang lebih baik.Kata Kunci: lagu berbahasa inggris, sumber belajar AbstractThe aim of the research was to add options on teaching sources for both lecturers and students. the question of the research was What is the students’ perception towards how English song help them in acquiring English? And Is there any correlation between the frequency of listening to English song with their performance in listening class? In order to answer those research questions, the researcher using survey research with help of two instruments, questionnaire and lecturer’s checklist. The participants for the research were 48 students of two listening for daily content classes. Based on the research findings, most of students regard that English song help them to achieve good performance in the class. this could be seen from the responds of the participants answering the questionnaire. Also, there is a significant correlation between the frequency of listening to English songs with students’ performance in the class. the students with who often listen to English songs and use it as media for learning have better score.Keywords: English songs, learning source